Dialogic Communication between Teachers and Students as a Condition for Interaction of Subjects of the Higher School Educational Process - Eremeeva, Guzel Rinatovna; Khamisovna, Ismaeva Farida (International journal of higher education, 2020)
The article is devoted to the issue of educational interaction and cooperation between teachers and students. The purpose of the study is to show the need for dialogic communication in educational activities, form knowledge, and develop educational cooperation skills, allowing students to take an active position in the educational process to help them adapt to interactive learning. The study's methodological base is the technology of sign-contextual learning, the implementation of which involves the use of active teaching methods. The article gives definitions of the concepts "communication", "dialogic communication", "subject". The principles of dialogic communication are highlighted. Experimental work was carried out in pedagogical classes with students of non-pedagogical specialties. Based on the thesaurus, questions, and tasks of the module, "Teaching Methods" were compiled, training was carried out using active methods. Systematic control was achieved by combining different types of work; however, a special role was played by testing, including computer testing. The result of developing communication-dialogue was the emergence of the participants' subjective positions in the dialogue, the formation of their experience of dialogic communication.